Strategi Komunikasi untuk Program Corporate Social Responsibility dalam Pemberdayaan Masyarakat - Arifin Saleh; Mislan Sihite (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2020)
Corporate social responsibility (CSR) is a company's commitment not only to increase financial benefits, but also to develop a holistic, institutional and sustainable social, economic and regional development (Suharto, 2008). In practice, CSR is often regarded as corporate giving, corporate philanthropy, and corporate community relations. CSR cannot be separated from the practice of community empowerment or often referred to as community development. What is the relationship between CSR and community empowerment and how is the communication strategy for the CSR program in an effort to empower the community? The methodology in this study is of literature review type. The technique of data collection is done by secondary data techniques obtained through searching relevant books, research results related to the topic of writing, mass media news, and relevant journals. The data obtained are then analyzed and completed with qualitative techniques by describing the data obtained to answer the existing debate. The results of the study found that CSR programs cannot be separated from community empowerment. One of the objectives of CSR is to create empowered communities, especially those around the company. In carrying out CSR activities for community empowerment, the role of a communication strategy is expected. The relevant communication strategies include mass communication and intercultural communication. By using these two communication strategies, it is expected that CSR programs for community empowerment will be more effective and efficient.